1992
DOI: 10.1007/bf01244472
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and thickness of the surface contaminations on STM tungsten tips, studied by AES/SEM and ARXPS

Abstract: Abstract. The combination of Auger electron spectroscopy (AES), scanning electron microscopy (SEM) and angle resolved X-ray photoelectron spectroscopy (ARXPS) has been applied to the analysis of the distribution of elements at the surface region of electrochemically etched tungsten tips and the determination of the thickness of a layer with oxygen and carbon contamination. Auger line profiling revealed a homogeneous distribution of oxygen and significant enrichment of carbon on the W tip between 0 and 1.5/~m f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Transmission electron microscopy (TEM) studies indicated that the tip was covered by thin (1−5 nm thick) polycrystalline tungsten oxides , and carbon or graphite layers. Auger electron spectroscopy (AES) combined with Ar + sputter profiling revealed a 1−3 nm thick oxide and carbon layer on W tips, and a W4f X-ray photoelectron spectroscopy (XPS) spectrum of etched W single crystal showed that the surface was comprised of tungsten carbide (WC) and tungsten trioxide (WO 3 ) …”
Section: Introductionmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) studies indicated that the tip was covered by thin (1−5 nm thick) polycrystalline tungsten oxides , and carbon or graphite layers. Auger electron spectroscopy (AES) combined with Ar + sputter profiling revealed a 1−3 nm thick oxide and carbon layer on W tips, and a W4f X-ray photoelectron spectroscopy (XPS) spectrum of etched W single crystal showed that the surface was comprised of tungsten carbide (WC) and tungsten trioxide (WO 3 ) …”
Section: Introductionmentioning
confidence: 99%
“…First experiments were carried out with W and Au tips. Electrochemically etched W tips provide apex radii of a few nanometres (Hacker et al, 1992), but they are covered with a thin oxide layer (Beigelsen et al, 1987;Lisowski et al, 1992), inducing unstable tunnelling currents, requiring frequent tip changes. For the vacuum hybrid STEM/STM this becomes a time-consuming task.…”
Section: Tipsmentioning
confidence: 99%